2018
DOI: 10.1158/1055-9965.epi-18-0243
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Review of Diet and Cutaneous Malignant Melanoma

Abstract: Incidence of cutaneous malignant melanoma has continued to rise despite public efforts to promote sun protection behaviors among populations at risk. However, dietary factors may also affect the development of melanoma. In the past few decades, findings from epidemiologic and experimental research have linked consumption of several foods and other nutrients to the risk of melanoma. Caffeine has been associated with a lower risk of melanoma, and citrus fruits and alcohol with increased risk. Associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 87 publications
0
25
0
1
Order By: Relevance
“…However, findings from epidemiologic studies investigating the association between vitamin D and risk of skin cancer remain inconsistent 22 . Several studies have indeed addressed the association between vitamin D and skin cancer risk 22 , 23 which has been studied by exploring intakes of dietary vitamin D (from food or supplements), or circulating levels of 25(OH)D (a biomarker of vitamin D status reflecting both intake and synthesis related to sun exposure). Regarding 25(OH)D levels, most of the studies suggested an increased risk of melanoma and KC 24 , 25 and some studies reported inverse 26 , 27 or null associations 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings from epidemiologic studies investigating the association between vitamin D and risk of skin cancer remain inconsistent 22 . Several studies have indeed addressed the association between vitamin D and skin cancer risk 22 , 23 which has been studied by exploring intakes of dietary vitamin D (from food or supplements), or circulating levels of 25(OH)D (a biomarker of vitamin D status reflecting both intake and synthesis related to sun exposure). Regarding 25(OH)D levels, most of the studies suggested an increased risk of melanoma and KC 24 , 25 and some studies reported inverse 26 , 27 or null associations 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…This could be useful for evaluating the balance between the potential benefits and risks for skin cancer prevention. In addition, previous epidemiologic studies have also yielded inconsistent results regarding the influence of dietary vitamin D on the risk of skin cancer 22 , 23 ; some studies suggested that a high intake of dietary vitamin D may protect against skin cancer development 27 , 35 , while other studies found null results 35 , 36 . Caini and colleagues observed no statistically significant association for the highest versus lowest intake of vitamin D in relation to skin cancer 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Several foods and nutrients have been shown to have protective effects against melanoma-genesis or synergic effects with the medications used for CMM treatment. Recent literature reviews and data from the World Cancer Research Fund describe the epidemiological aspects of the interactions between diet and melanoma [154, 155]. In the present review, we focused mainly on recent advances regarding the biological mechanisms which lay under such interactions, involving specific compounds of current active research.…”
Section: Discussionmentioning
confidence: 99%
“…Western diets are also characterized by excessive intake of alcohol [ 273 ], which can impact MM [ 274 ]. Chronic alcohol intake, especially in combination with HFD results in persistent ketonuria associated with increased serum levels of acetoacetate [ 275 ], which accelerates BRAF V600E -MEK1 signaling.…”
Section: Environmental Factors Upregulating Mir-21mentioning
confidence: 99%